Contestation of Interests in Nickel Downstreaming Policy In Indonesia: an Analysis of the Advocacy Coalition Framework - Lorenza, Leuryan Cherry; Dewi, Dian Suluh Kusuma; Juwitaningsih, Ekapti Wahjuni D (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
This research analyzes the contestation of interests in Indonesia's nickel downstreaming policy using the Advocacy Coalition Framework (ACF). Utilizing a qualitative case study method, the study identifies a competition between two primary coalitions: the "Nationalist-Industrialist Coalition," dominated by the central government and industrial players, and the critical "Pro Market & Environment Coalition". The government coalition dominates the policy landscape, driven by core beliefs in economic sovereignty and national industrialization. Conversely, the critical coalition highlights impact such as environmental degradation and social inequality affecting local communities. External factors, including global demand for nickel in electric vehicle batteries and WTO trade disputes, have paradoxically strengthened the stability of the national policy. The study recommends enhancing inter-agency coordination to mitigate global legal risks and the resulting environmental impacts.